MELATIH KEMAMPUAN COMPUTATIONAL THINKING MELALUI MEDIA PEMBELAJARAN IPA BERBASIS UNPLUGGED PADA SISWA KELAS V SDN 37 PEKANBARU - Azura Salsabilla; Muthyara Sadillah; Nailah Ansariah; Rizka Munthia; Neni Hermita; Rifqa Gusmida Syahrun Barokah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The integration of computational thinking (CT) into classroom instruction has become increasingly important in 21st-century education due to its role in fostering logical reasoning, systematic thinking, and problem-solving skills among learners. However, implementing CT at the elementary school level requires instructional approaches that are developmentally appropriate and accessible to young learners through concrete learning experiences. This study aimed to examine the development of elementary students’ CT skills through science learning media based on unplugged coding in the topic of Harmony in Ecosystems. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed involving 24 fifth-grade students at SDN 37 Pekanbaru. The intervention was carried out using a student worksheet integrating unplugged coding activities, including coordinates, conditionals, debugging, and classification within a science learning context. Data were collected through an objective test developed based on CT indicators and analyzed using descriptive statistics and N-Gain analysis. The findings revealed an improvement in students’ CT skills, indicated by an increase in the mean score from 6.88 to 8.75, with an N-Gain score of 0.60 categorized as moderate. These findings suggest that integrating unplugged coding activities into science instruction provides contextual learning experiences, encourages active student engagement, and supports the development of more structured thinking patterns in understanding scientific concepts.